2023
DOI: 10.7759/cureus.34371
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus As Possible Prodromal Manifestation of COVID-19: A Report of Two Cases

Abstract: Although the etiopathology of normal pressure hydrocephalus (NPH) is still not completely defined, several studies in recent years have highlighted the role of neuro-inflammation mediators in its development.During COVID-19, the infected host develops a multifaceted inflammatory syndrome, that may lead to an uncontrolled immune system response also localized in the host nervous system. In fact, the target of the viral Spike protein, the angiotensin-converting enzyme 2 (ACE2) receptors, is widely expressed in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The belief that COVID-19 infection could act as a triggering factor for the development of CSF dynamic disorder (eventually leading to deterioration of previously diagnosed hydrocephalus), is supported by some case reports included in our review [ 14 - 15 ]. Torelli et al [ 14 ] described a case of a 79-year-old unvaccinated man with a history of idiopathic normal pressure hydrocephalus who experienced a worsening of his neurological status during acute COVID-19 infection.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The belief that COVID-19 infection could act as a triggering factor for the development of CSF dynamic disorder (eventually leading to deterioration of previously diagnosed hydrocephalus), is supported by some case reports included in our review [ 14 - 15 ]. Torelli et al [ 14 ] described a case of a 79-year-old unvaccinated man with a history of idiopathic normal pressure hydrocephalus who experienced a worsening of his neurological status during acute COVID-19 infection.…”
Section: Discussionsupporting
confidence: 58%
“…The belief that COVID-19 infection could act as a triggering factor for the development of CSF dynamic disorder (eventually leading to deterioration of previously diagnosed hydrocephalus), is supported by some case reports included in our review [ 14 - 15 ]. Torelli et al [ 14 ] described a case of a 79-year-old unvaccinated man with a history of idiopathic normal pressure hydrocephalus who experienced a worsening of his neurological status during acute COVID-19 infection. Dai et al [ 15 ] reported a case of a 29-year-old female with a history of non-VP shunt-requiring congenital stenosis of the middle cerebral aqueduct.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations